Pengaruh Kualitas Pelayanan Dan Store Atmosphere Terhadap Kepuasan Konsumen Pada Miso Pak Imam Pekanbaru - Laras Azzahra; Endang Sutrisna (Komunitas Dosen Indonesia, 2023)
This study aims to determine and analyze the influence of service quality and store atmosphere on customer satisfaction at Miso Pak Imam Pekanbaru. The method used in this research is descriptive and quantitative statistics. Data collection was carried out using a questionnaire consisting of 24 statements and the sample consisted of 100 respondents using accidental sampling technique. Research data was collected using a questionnaire that was measured using a likert scale and processed using SPSS 26 to process data and test hypotheses. The test result in this study show that partially the service quality variable (X1) has a positive and significant effect on customer satisfaction, partially the store atmosphere variable (X2) has a positive and significant effect on customer satisfaction. Simultaneously service quality (X1) and store atmosphere (X2) have a positive and significant influence on customer satisfaction.